A Review of Ammonia Combustion and Emissions Characteristics in Spark-Ignition Engines and Future Road Map - Vikas Sharma; Angad Panesar; Guillaume de Sercey; Steven Begg (Energies)
Ammonia (NH3) is gaining recognition as a viable “green” transportation fuel due to its zero-carbon characteristic, its high energy density and its widespread availability. However, NH3 has a high auto-ignition temperature, resulting in potential emissions of NOx and unburned NH3. Addressing combustion challenges requires innovative solutions, such as the application of combustion promoters to enhance NH3 combustibility. This review article focuses on the compatibility of NH3 as a fuel for spark-ignition (SI) engines, examining its combustion under various modes including pure NH3 combustion, gasoline blends, NH3/hydrogen (H2) blends, and NH3/natural gas blends in single or dual-fuel configurations. The formation of nitrogen oxides (NOx) and slip-NH3 is explored to understand emissions species such as NO and N2O. Additionally, the article highlights the limitations of NH3 as a fuel for SI combustion. The comprehensive discussion provided in this review aims to fill a critical gap in the literature regarding NH3’s feasibility as a zero-carbon fuel for SI engines, particularly in the maritime sector. By offering insights into NH3 combustion characteristics and emissions profiles, the article seeks to provide a roadmap for leveraging NH3 as a suitable non-carbon fuel to decarbonize the marine sector and advance global sustainability goals.